PENERAPAN METODE DE NOVO PROGRAMMING DALAM PERENCANAAN PRODUKSI STICK KENTANG PADA UKM DELIMA BANDARA DI KAB. PADANG PARIAMAN - Amelja, Vania; Helma, Helma (Journal of Mathematics UNP, 2023)
This research is an applied research conducted aimed at determining how much potato stik products should be produced by UKM Delima Bandara. The De Novo Programming method is used to plan the production of potato sticks in order to generate maximum profits. The data used are primary data, namely data, demand data, raw material availability data, production cost data, and sales price data in 2022. Based on the results of production calculation by rill, UKM Delima Bandara obtained a profit for a years of Rp. 400.626.000, while the profit of the industry if its production planning using the method of De Novo Programming gains a profit of Rs. 410,860,000 in one year. Therefore, with the application of the De Novo Programming method, UKM Delima Bandara can plan production and save use raw materials so as to obtain better profit generation planning with the amount of production of original potato stiks as much as 1.476 kg, cheese potato stiks as much as 1.278 kg, lime leaf potato stiks as much as 1.269 kg, onion potato stiks as much as 1.398 kg, and balado potato stiks as much as 1.237 kg.